A two‐centre experience of transanal total mesorectal excision. (December 2016) - Buchs, N. C.; Wynn, G.; Austin, R.; Penna, M.; Findlay, J. M.; Bloemendaal, A. L. A.; Mortensen, N. J.; Cunningham, C.; Jones, O. M.; Guy, R. J.; Hompes, R.
Abstract: Aim: Transanal total mesorectal excision (TaTME) offers a promising alternative to the standard surgical abdominopelvic approach for rectal cancer. The aim of this study was to report a two‐centre experience of this technique, focusing on the short‐term and oncological outcome. Method: From May 2013 to May 2015, 40 selected patients with histologically proven rectal adenocarcinoma underwent TaTME in two institutions and were prospectively entered on an online international registry. Results: Forty patients (80% men, mean body mass index 27.4 kg/m 2 ) requiring TME underwent TaTME. Procedures included low anterior resection ( n  =   31), abdominoperineal excision ( n  =   7) and proctocolectomy ( n  =   2). A minimally invasive approach was attempted in all cases, with three conversions. The mean operation time was 368 min and 16 patients (40%) had a synchronous abdominal and transanal approach. There was no mortality and 16 postoperative complications occurred, of which 68.8% were minor. The median length of stay was 7.5 (3–92) days. A complete or near‐complete TME specimen was delivered in 39 (97.5%) cases with a mean number of 20 lymph nodes harvested. R0 resection was achieved in 38 (95%) patients. After a median follow‐up of 10.7 months, there were no local recurrences and six (15%) patients had developed distant metastases. Conclusion: TaTME appears to be feasible, safe and reproducible, without compromising the oncological principles of rectal cancer surgery. It is an attractive option for patients for whom laparoscopy is likely to be particularly difficult. These encouraging results should encourage larger studies with assessment of long‐term function and the oncological outcome.